Undergraduate Research and Its Impact on Student Success for Underrepresented Students. Issue 169 (March 2015) - O'Donnell, Ken; Botelho, Judy; Brown, Jessica; González, Gerardo M.; Head, William
Abstract : This chapter captures the mission and spirit of the California State University in its efforts to institutionalize undergraduate research and support the success of students traditionally underrepresented in higher education.